Pseudomonas aeruginosa Regulatory Protein AnvM Controls Pathogenicity in Anaerobic Environments and Impacts Host Defense - Yingchao Zhang (American Society for Microbiology, 2019)
ABSTRACT Pseudomonas aeruginosa, one of the most common pathogens in hospital-acquired infections, is tightly controlled by a multilayered regulatory network, including the quorum sensing system (QS), the type VI secretion system (T6SS), and resistance to host immunity. We found that the P. aeruginosa 3880 (PA3880) gene, which encodes an unknown protein, acts as a regulator of anaerobic metabolism in response to oxidative stress and virulence in P. aeruginosa. More than 30 PA3880 homologs were found in other bacterial genomes, indicating that PA3880 is widely distributed in the Bacteria kingdom as a highly conserved gene. Deletion of the PA3880 gene changed the expression levels of more than 700 genes, including a group of virulence genes, under both aerobic and anaerobic conditions. To further study the mechanisms of PA3880-mediated regulation in virulence, we utilized a bacterial two-hybrid assay and found that the PA3880 protein interacted directly with QS regulator MvfR and anaerobic regulator Anr. Loss of the PA3880 protein significantly blunted the pathogenicity of P. aeruginosa, resulting in increased host survival, decreased bacterial burdens, reduced inflammatory responses, and fewer lung injuries in challenged mice hosts. Mechanistically, we found that Cys44 was a critical site for the full function of PA3880 in influencing alveolar macrophage phagocytosis and bacterial clearance. We also found that AnvM directly interacted with host receptors Toll-like receptor 2 (TLR2) and TLR5, which might lead to activation of the host immune response. Hence, we gave the name AnvM (anaerobic and virulence modulator) to the PA3880 protein. This characterization of AnvM could help to uncover new targets and strategies to treat P. aeruginosa infections. IMPORTANCE Infections by Pseudomonas aeruginosa, one of the most frequently isolated human pathogens, can create huge financial burdens. However, knowledge of the molecular mechanisms involved in the pathogenesis of P. aeruginosa remains elusive. We identified AnvM as a novel regulator of virulence in P. aeruginosa. Deletion of anvM altered the expression levels of more than 700 genes under aerobic and anaerobic conditions, including quorum sensing system genes and oxidative stress resistance genes. AnvM directly interacted with MvfR and Anr, thus regulating their downstream genes. More importantly, AnvM directly bound to TLR2 and TLR5, which turn on the host immune response. These findings provide insights into the significance of AnvM homologs in pathogenic bacteria and suggest a potential drug target against bacterial infection.